Clinical validation of a second generation anti‐SARS‐CoV‐2 IgG and IgM automated chemiluminescent immunoassay. Issue 4 (26th January 2021) - Pieri, Massimo; Nuccetelli, Marzia; Nicolai, Eleonora; Sarubbi, Serena; Grelli, Sandro; Bernardini, Sergio
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has proven to be extremely contagious and has spread rapidly all over the world. A key aspect in limiting the virus diffusion is to ensure early and accurate diagnosis. Serological assays could be an alternative in increasing testing capabilities, particularly when used as part of an algorithmic approach combined with molecular analysis. The aim of this study was to evaluate the diagnostic accuracy of a second generation chemiluminescent automated immunoassay able to detect anti‐SARS‐CoV‐2 immunoglobulin G (IgG) and immunoglobulin M (IgM) antibodies. Data are carried out on healthy subjects and other infectious diseases pre‐pandemic sera, as controls, and on two different coronavirus disease 2019 hospitalized patient groups (early and late infection time). Data obtained have been analyzed in terms of precision, linearity, sensitivity and specificity. Specificities are: 100% for anti‐SARS‐CoV‐2 IgG and 98% for anti‐SARS‐CoV‐2 IgM, in all patient groups. Sensitivities are: 97%, 100%, and 98% for anti‐SARS‐CoV‐2 IgG and 87%, 83%, and 86% for anti‐SARS‐CoV‐2 IgM in the early infection, in the late infection and in the total patient group, respectively. The Mindray anti‐SARS‐CoV‐2 IgG and IgM assays demonstrated higher sensitivity and specificity, indicating that IgG and IgM simultaneous detection is useful even in the early phases of infection.